How to prove is two variables or a graph is exponential

Watch
Adam_1999
Badges: 8
Rep:
?
#1
Report Thread starter 2 years ago
#1
Suppose we have two graphs of y against x. Graph 1 has the equation y = A . b^-x where and b are constants. Graph 2 has equation y = P . x^-1. Both of the graphs do not show a y intercept on them.

How do we tell them apart? They will look the same. We do it by by choosing 3 values of x which are equally spaced apart. By equally spaced I mean difference between each x value is the same. An example would be x = 2, x = 4 and x = 6.

Suppose we choose three x values X1, X2 and X3. We now need to go and read off the corresponding of y, Y1, Y2 and Y3. If the graph is exponential, Y1/Y2 = Y2/Y3.

This is because Y1 = A . b^-X1, Y2 = A . b^-X2 and so on.

Now: Y1/Y2 = (A . b^-X1)/(A . b^-X2) = b^(-X1 + X2) = b^(X2 - X1). The A s cancel and we can use the law that states a^n / a^m = a^(n-m).

Doing the same for Y2/Y3 gives: Y2/Y3 = (A . b^-X2)/ (A . b^-X3) = b ^(-X2 + X3) = b^(X3 - X2).

Now we are saying that b^(X2 - X1) = b^(X3 - X2). This makes sense because X2 - X1 = X3 - X2, as the difference between X1, X2 and X3 is the same (see the second paragraph).

This method will not work for graph 2. For this graph, Y1 = P/X1, Y2 = P/X2 and so on.

Y1/Y2 = X2/X1 and Y2/Y3 = X3/X2. The two expressions would not be equal.

You do need to know this for A Level.
0
reply
Kyx
Badges: 6
Rep:
?
#2
Report 2 years ago
#2
(Original post by Adam_1999)
Suppose we have two graphs of y against x. Graph 1 has the equation y = A . b^-x where and b are constants. Graph 2 has equation y = P . x^-1. Both of the graphs do not show a y intercept on them.

How do we tell them apart? They will look the same. We do it by by choosing 3 values of x which are equally spaced apart. By equally spaced I mean difference between each x value is the same. An example would be x = 2, x = 4 and x = 6.

Suppose we choose three x values X1, X2 and X3. We now need to go and read off the corresponding of y, Y1, Y2 and Y3. If the graph is exponential, Y1/Y2 = Y2/Y3.

This is because Y1 = A . b^-X1, Y2 = A . b^-X2 and so on.

Now: Y1/Y2 = (A . b^-X1)/(A . b^-X2) = b^(-X1 + X2) = b^(X2 - X1). The A s cancel and we can use the law that states a^n / a^m = a^(n-m).

Doing the same for Y2/Y3 gives: Y2/Y3 = (A . b^-X2)/ (A . b^-X3) = b ^(-X2 + X3) = b^(X3 - X2).

Now we are saying that b^(X2 - X1) = b^(X3 - X2). This makes sense because X2 - X1 = X3 - X2, as the difference between X1, X2 and X3 is the same (see the second paragraph).

This method will not work for graph 2. For this graph, Y1 = P/X1, Y2 = P/X2 and so on.

Y1/Y2 = X2/X1 and Y2/Y3 = X3/X2. The two expressions would not be equal.

You do need to know this for A Level.
Thanks


Posted from TSR Mobile
0
reply
X

Quick Reply

Attached files
Write a reply...
Reply
new posts
Back
to top
Latest
My Feed

See more of what you like on
The Student Room

You can personalise what you see on TSR. Tell us a little about yourself to get started.

Personalise

Are you worried that a cap in student numbers would affect your place at uni?

Yes (196)
60.31%
No (71)
21.85%
Not sure (58)
17.85%

Watched Threads

View All